The Challenges of EFL Learners in Higher Education to Participate the Online Presentations - Dian Wahyu Saputri; Paulina Besty Fortinasari (Journal of English Language Teaching and Cultural Studies, 2022)
Not only presenters but also participants can affect the process of online classroom presentations, including the discussion in question-and-answer sessions. Sometimes, several EFL learners who participate in online classroom presentations do not actively join the discussion by asking the presenters questions, suggestions, or objections. Various reasons may affect the issues, including the challenges the participants face. Therefore, this study aims to determine the challenges of EFL learners as participants during online classroom presentations. The participants were 23 sixth-semester students from English Department, Universitas Tidar. The researchers used descriptive qualitative methods and questionnaires as instruments to collect and analyze the data. The researchers found that 61% of the respondents often and sometimes joined the discussion, and 39,1% of the respondents rarely joined the discussion. The researchers conclude that many students actively join the discussion in question-and-answer sessions, but the number of students who did not actively join the discussion is relatively high. The reasons are the challenges faced by the EFL learners related to the low confidence, anxiety, and noise from the presenters and the participants during online classroom presentations. Based on the data, the students prefer using the chat box to the microphone to join the discussion.